SOME PHYSICAL PROPERTIES OF ESSENTIAL OIL OF BARAKASEED NIGELLA SATIVA L. IMPACTED BY BAT GUANO Otonycteris hemprichii Camd AND SEAWEED EXTRACT - & et al., Al-mohammedi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
Some fertilizers practices could be used to improve Baraka seed Nigella sativa L. as a medicinal crop like organic farmyard manure which efficiently applied to enhance growth and yield. Thus, a field experiment was conducted out at Research Station in Tikrit-Iraq during 2012/2013 season to estimate the impact of bat guano (0, 75, 125 and 175 kg.ha-1), seaweed extract as kelpak (0, 1, 2 and 3ml.l-1) on some physical and chemical essential oil components. Two factors were arranged in factorial experiment in randomized complete block design with three replicates. Thus, results revealed that application of bat guano at 125 kg.ha-1 was superior in enhancement of essential oil and its some physical and chemical properties as essential oil% of 1.53%, specific gravity of 0.95 g.cm-3, refractive index of 1.82, essential oil density of 0.93, dithymohydroquinone of 37.44µg.µl-1 and thymol of 25.73 µg.µl-1. Moreover, kelpak (3ml.l-1) significantly improved physical and chemical properties of essential oil which were essential oil% of 1.52%, specific gravity of 0.93 g.cm-3, refractive index of 1.72, and essential oil density of 0.94 and thymol of 25.92 µg.µl-1. Whereas, the main component dithymohydroquinone effected by application of 2 ml.l-1kelpak of 37.04 µg.µl-1. It could be recommended to use bat guano as alternative to chemical fertilizer fortified with foliar application of seaweed extract as kelpak so as to improve physical and chemical properties of essential oil.